SELF-ACCEPTANCE OF SINGLE MOTHERS WITH MULTIPLE DISABILITIES: Case Study in Lakarsantri, Surabaya - Aisha Nadya; Dwi Jayanti Kurnia Dewi; Dika Putri Rahayu (PG PAUD Universitas Negeri Surabaya, 2024)
Single mothers who have young children with multiple disabilities have full responsibility for raising children, without the presence of a partner who acts as both mother and father for their children. Single mothers who raise children with multiple disabilities face extra challenges and difficulties compared to other parents. Various challenges for single mothers include meeting the special needs of children, limited access to services and support, to multiple financial and emotional burdens. Self-acceptance is a crucial factor that affects the well-being and quality of life of single mothers with children with multiple disabilities. This study was conducted to explore and understand more deeply the phenomenon of self-acceptance in single mothers with children with multiple disabilities using a qualitative approach. The method used is a case study involving single mother participants who have young children with multiple disabilities, living in the Lakarsantri area, Surabaya. The multiple disabilities experienced by the subject's child are hard of hearing and low vision. This research method uses observation, interviews, and documentation. The data analysis technique uses thematic analysis. The process of accepting the child's condition is a journey in itself for single mothers through five stages, namely denial, depression, anger, bargaining, and finally acceptance and adjustment. This process involves seeking knowledge, consulting with professionals, and interacting with other families who have similar experiences. Emotional fluctuations are still possible, especially when parents are faced with new challenges in their child's development. Self-acceptance is better seen as an active process in which parents continually adjust, learn, and grow with their children.